Makna dan Hakikat Kebebasan dalam Islam - Mujahid, Kasori; Hadiwijaya, Lalu Firman (Lembaga Yasin AlSys, 2025)
This study examines the meaning and essence of freedom in Islam, focusing on its relevance in the context of modern life. Through a qualitative approach based on literature review, this research analyzes various dimensions of freedom in Islam, including spiritual, socio-political, economic, and intellectual aspects. The findings indicate that the concept of freedom in Islam possesses unique characteristics that distinguish it from secular notions of freedom, where freedom is understood as a right inherently linked to spiritual and social responsibilities. The study also reveals that the implementation of Islamic values of freedom in the modern era requires an adaptive and contextual approach, while still adhering to the fundamental principles of the religion. These findings provide a significant contribution to the development of a framework of understanding that can assist Muslim communities in appropriately implementing the concept of freedom in contemporary times.